Perkembangan Musik Campursari di Yogyakarta tahun 1990-2019: Dari Manthous hingga Didi Kempot (Lembaga Pengembangan Kinerja Dosen, 2025)
Campursari music is a form of fusion between traditional Javanese music and modern music that has developed rapidly in Yogyakarta since the 1990s. This genre is a symbol of cultural acculturation through musical innovation that is able to bridge local values ​​and developments in the era. This study uses a historical research method with four stages, namely: heuristics (collecting sources), verification (criticizing sources), interpretation (interpreting the meaning of historical data), and historiography (writing history). The focus of the research is directed at the role of important figures such as Manthous and Didi Kempot in shaping and developing the characteristics of Campursari during the period 1990–2019. Manthous introduced Campursari by combining elements of gamelan and Javanese langgam, and maintaining typical musical structures such as pelog, slendro, and tembang macapat. Meanwhile, Didi Kempot presents a new color with a pop-keroncong-dangdut style that is more flexible, emotional, and popular, especially among the younger generation. The differences in the use of instruments, lyrical themes, and musical approaches show the transformation of Campursari from traditional roots to the contemporary realm. Campursari's popularity has increased through mass media and fan communities such as